Factors Affecting the Decisions on Choosing Logistics Service Providers in Food industry in Thailand - et. al., Ampika Laoprawatchai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Logistic services are the essential factors to enhance the organizational performance and the selection of logistic services provided is the foremost issue nowadays. Thus, the present article analyze the impact of logistic providers’ reliability, responsiveness and assurance on the selection decision of logistic services providers in food industry of Thailand. This article also investigates the moderating role of organizational satisfaction among the relationships of logistic providers’ reliability, responsiveness, assurance and selection decision of logistic services providers in food industry of Thailand. The primary data collection methods such as questionnaires were used to gather the data and smart-PLS was used for analysis purpose. The results have revealed that logistic providers’ reliability, responsiveness and assurance have positive association with the selection decision of logistic services providers in food industry of Thailand. The findings also indicated that organizational satisfaction significantly moderates among the nexus of logistic providers’ reliability, responsiveness and selection decision of logistic services providers in food industry of Thailand. This study is suitable for the policymakers that they should improve their focus towards logistic services providers’ selection that could improve the organizational performance.